IMPLEMENTASI MANAJEMEN KELAS DALAM PROSES MENGHAFAL AL-QUR’AN DI PONDOK PESANTREN TOHIR YASIN LOMBOK - M. Sobry (Universitas Islam Negeri Mataram, 2021)
Memorizing the Qur'an is a process of remembering, preserving, memorizing, preserving the Qur'an starting from Surah al-Fatihah to Surah an-Nas for the sake of maintaining its purity and avoiding falsification. Memorizing activities will run if managed properly so that the targets to be achieved can be achieved. The class division made by Diniah Tahfiz Pesantren Tohir Yasin is nothing but in order to achieve its mission, namely that students who enter the tahfiz class can finish memorizing the Qur'an in 2 years and no later than 3 years. This research is a field research with a phenomenological qualitative approach, data collection is done by technique (1). Observation (2). In-depth interviews with informants. (3). Documentation. The data analysis technique was carried out using the Miles and Huberman model: data collection, data reduction, data display, and conclusion drawing/verification. While the validity of the data test includes: Extension of research and triangulation. The findings of the study showed that the division of the tahfiz class into several classes was effective and efficient as evidenced by the presence of a tahfiz plus student who could memorize up to 25 juz within 6 months and at least up to 8 juz.